1993
DOI: 10.1177/096120339300200505
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus in Greece. Clinical Features, Evolution and Outcome: a Descriptive Analysis of 292 Patients

Abstract: The purpose of this study was the descriptive analysis of patients with systemic lupus erythematosus (SLE) with a particular focus on initial clinical features, evolution and outcome of disease, prevalence of clinical and serological manifestations and identification of clinicoserological associations indicative of renal and CNS involvement. The methodology applied was the following: retrospective analysis of the clinical charts of 292 unselected patients (246 female (84.2%) and 46 male (15.7%)) with SLE exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 53 publications
6
39
1
4
Order By: Relevance
“…About the clinical-serologic profile, our study substantially confirms what has been previously reported by some authors [12][13][14], but not by all [15], who had emphasized how skin involvement (especially discoid rash) and joints symptoms (arthritis) seem to be negatively related to the presence of NP manifestations. In our study, also leukopenia and hemolytic anemia were more frequently found among SLE patients without NP involvement.…”
Section: Discussionsupporting
confidence: 91%
“…About the clinical-serologic profile, our study substantially confirms what has been previously reported by some authors [12][13][14], but not by all [15], who had emphasized how skin involvement (especially discoid rash) and joints symptoms (arthritis) seem to be negatively related to the presence of NP manifestations. In our study, also leukopenia and hemolytic anemia were more frequently found among SLE patients without NP involvement.…”
Section: Discussionsupporting
confidence: 91%
“…All patients fulfilled the American College of Rheumatology criteria for the classification of SLE (4). Sera from 80 patients with rheumatoid arthritis (RA) (5), 40 with anemia (hemoglobin [Hgb] 5 1 2 gmidl) and 40 without anemia, were used as disease controls. No patients in this study received EPO for therapeutic use.…”
Section: Methodsmentioning
confidence: 99%
“…SLE is accompanied by arthritis/arthralgias, cutaneous rash, vasculitis, and involvement of the central nervous system, with renal and cardiopulmonary manifestations (7,8), whereas the common feather of RA is a predominant synovial proliferation, a destruction of the articular cartilage associated with macrophages and activated T-cell infiltration in and around the joints (9). The relationship between different types of autoantibodies and especially their relationship to RA or SLE remain unclear.…”
mentioning
confidence: 99%